PENGGUNAAN MODEL CAPITAL ASSET PRICING MODEL (CAPM) DALAM PENGAMBILAN KEPUTUSAN INVESTASI PADA SAHAM JAKARTA ISLAMIC INDEX (JII) - Raja Ria (UIR Press, 2022)
The purpose of this study is to analyze the use of the Capital Asset Pricing Model (CAPM) as the basis for making investment decisions for stocks listed on the Jakarta Islamic Index (JII) for the period June 2019 – June 2021. The type of research used in this study is quantitative research with a descriptive approach. . The object of this study is all stocks listed on the Jakarta Islamic Index (JII) for the period June 2019 – June 2021. The sampling technique used is purposive sampling. The sample in this study were 19 stocks. The results of this study indicate that: (1) CAPM can be used in assessing efficient and inefficient Jakarta Islamic Index (JII) stocks (2) There are 10 stocks that include Efficient stocks, namely ADRO, AKRA, ANTM, BRPT, BTPS, CPIN , EXCL, INCO, JPFA, SCMA. These shares have a value of Ri > ERi. The investment decision that must be made by investors is to buy efficient shares